2000
DOI: 10.4314/sajas.v30i3.3855
|View full text |Cite
|
Sign up to set email alerts
|

Pre-weaning growth traits of the Hereford breed in a multibreed composite beef cattle population

Abstract: Data from a multibreed composite beef cattle population, managed under intensive irrigated grazing conditions, were used to estimate direct additive heritabilities (h 2 a ), maternal heritabilities (h 2 m ) and maternal permanent environmental effects (c 2 ) for birth weight (BW) and weaning weight (WW) of the calf and cow efficiency of the dam (CE: WW/dam weight 0.75 x 100). Calves born between 1968 and 1993 (n = 52628) had varying levels of Hereford genes, ranging from 0% to 100%, with an average of 19.3%. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The higher heritability obtained in this study is in agreement with the findings of Schoeman and Jordaan (1999) and Skrypzeck et al (2000) who found a higher direct heritability estimates of 0.62 and 0.72 for birth weight, respectively. Both authors mentioned that fairly high heritability, arising from large genetic variances due to the multibreed composition of the herd could have been expected, since the population consists of 15 breeds and this effect was not accounted for by the model.…”
Section: Discussionsupporting
confidence: 92%
“…The higher heritability obtained in this study is in agreement with the findings of Schoeman and Jordaan (1999) and Skrypzeck et al (2000) who found a higher direct heritability estimates of 0.62 and 0.72 for birth weight, respectively. Both authors mentioned that fairly high heritability, arising from large genetic variances due to the multibreed composition of the herd could have been expected, since the population consists of 15 breeds and this effect was not accounted for by the model.…”
Section: Discussionsupporting
confidence: 92%
“…For Hereford, the direct additive effect for BW was positive in some reports (Gregory et al, 1978;Schoeman et al, 1993), but negative in other crossbreeding studies (Alenda et al, 1980;Skrypzeck et al, 2000a). Skrypzeck et al (2000b) assessed the contribution of the Hereford breed in the same multibreed beef cattle herd and suggested higher levels of Hereford contributions in crossbreeding for the prevention of dystocia. In another investigation Hereford sires were used also on heifers of other breeds to decrease the incidence of dystocia (Tawonezvi et al, 1988).…”
Section: Resultsmentioning
confidence: 97%
“…The direct and indirect heritability estimates for mass were of comparable magnitude to those reported for mammals and birds (Cheverud et al ., 1983; Aggrey & Cheng, 1993; Smith & Wettermark, 1995; Skrypzeck et al ., 2000; Neser et al ., 2001). These results suggest that indirect genetic effects of parental care performance generally play an important role in increasing the genetic variance of body mass and size, independently of taxon, and thus accelerate the response of body mass and size to natural selection.…”
Section: Discussionmentioning
confidence: 99%